Isolation and identification of probiotic Bacillus subtilis AJQ03 from the intestinal tract of Anguilla japonica (Japanese eel) - Wang, Xi; Yao, Yuxin; Ge, Hui; Zhang, Jiaonan; Zhang, Jiaolin; Yan, Qingpi (Frontiers in Microbiology, 2024)
In recent years, the use of fish-derived probiotics in aquaculture has become more widespread.However, research on Anguilla japonica-derived probiotics is still limited. To evaluate the potential of probiotics for disease control in eel aquaculture, isolates were obtained from the intestinal tract of healthy Anguilla japonica. These isolates were assessed for their adhesion properties, inhibition of pathogen adhesion, and hydrolytic enzyme production. Morphological characteristics and 16S rRNA sequence analysis were used for identification. Results showed that the AJQ03 strain adhered to the intestinal mucus and inhibited common pathogenic bacteria through adhesion inhibition, and further produced amylase, lipase, protease, and cellulase. Based on morphological characteristics and 16S rRNA sequencing, AJQ03 was identified as Bacillus subtilis. The strain demonstrated tolerance to various extreme conditions, as well as survival in simulated gastrointestinal fluids and superior growth in intestinal fluid compared to Luria-Bertani (LB) broth. In vitro safety tests showed that AJQ03 was not resistant to 32 antibiotics and exhibited γ hemolysis on blood plate. In vivo safety tests demonstrated a 100% survival rate for the fish, with stable organ indices, reduced bacterial loads in the liver and spleen, and complete bacterial clearance by day 7 without residue. Intestinal bacterial load results confirmed effective colonization by strain AJQ03. Analysis of the impact of AJQ03 on the gut microbiota of A. japonica revealed a significant increase in the relative abundance of Bacillus at the genus level, corroborating the colonization efficiency of AJQ03. Additionally, the relative abundances of Klebsiella, Pseudomonas, and Aeromonas were significantly lower compared to the controls, indicating that strain AJQ03 effectively reduced harmful bacteria and improved gut microbiota composition. This study confirms that B. subtilis AJQ03, isolated from the intestine of A. japonica, can serve as a probiotic candidate in A. japonica aquaculture.